Sentiment analysis and social networking sites: a case study - Mishra, Dr. Deepanjali (International Journal of Engineering and Technology, 2018)
Sentiments are the hormones of social networking sites. They trigger human emotions and emotions initiate social communication. All raw and polished communication that happen in social networking sites in form of chats, comments, scraps, tags, likes, photographs, etc are the result of an outpour of the bag of human sentiments. The objective of this research paper is to make an attempt to identify the various factors for identifying the role played by social networking sites on human emotions Social media is such a development that modern technology would always boast of, yet it cannot be denied that this media primarily functions with sentiments. Sentiments are to social media what fuel is to fire. Whether it is youth or age, whether it is house or office, whether it is man or woman every section of the society has contributed to the working, development and sustenance of the social media. Society, in other words, has fallen prey to these social networking sites. And the fundamental cause behind such addiction is "the role sentiments playâ€ in them. Too much of sentiments seasoned with a pinch of logic sometimes provide us with a real fun platform for our society. Perpetual exchange of emotions in social networking sites are the main reason responsible for making them our most emphatic guardian who is considered to be the most trustworthy companion. However, disastrous bargain with the human sentiments in social networking sites may prove to be harmful and hazardous. The paper intends to explore this intense association of sentiments with social networking sites with identification of various steps to createawareness and to be excessively involved with the virtual world that may lead to disastrous effects. This study will help various other research activities carried out in information andmanagement field as well firms planning to adopt and implement the possible ways of removing ignorance and open up various scope of research on the topic of social networking sites.